Drug utilisation pattern in dermatology outpatient department at a tertiary care hospital - Lakshmi, G. N. S. Sangeetha; Priyanka, Chilukuri; Vineela, Mortha (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Skin is the part of integumentary system that constitutes the largest organ of human body and thus it is exposed to injury by various extrinsic and intrinsic factors. The skin disorders have serious detrimental effect on quality of life of the general population. The present study was planned to define the prescription pattern in terms of rationality, drug interactions and financial burden of disease to the individual. Also, in the identification of problems related to drug use such as poly-pharmacy and drug-drug interaction. Methods: The present study was conducted in the male and female out-patient Department of Dermatology at a Tertiary Care Hospital in Hyderabad, Telangana over a period of two months. Prescriptions of 400 patients were analyzed i.e. 200 each were taken from the male and female OPD patients. An observational and cross-sectional study design was adopted for this study. Results: Prescriptions of 400 patients were analyzed. The average number of drugs per prescription was 3.73 in male OPD and 3.59 in female OPD. The percentage of generic drugs prescribed was 84.13% in male OPD and 77.3% in female OPD, drugs prescribed by brand name was 15.82% in male OPD and 22.7% in female OPD. Antihistamines were the most commonly prescribed drugs followed by antibacterial in female OPD and antifungals in male OPD. Conclusions: Prescription of maximum drugs was by their generic name and was dispensed free of cost to the patients from the hospital pharmacy. Almost all the drugs prescribed as oral formulation were present in the NLEM, India 2011. Whereas some topical formulations prescribed are not present in the NLEM. Therefore, were prescribed by trade name. Regular educational interventions like sensitization on pharmacovigilance may further promote rational prescribing.